Fatigue strength of several dental ceramics indicated for CAD-CAM monolithic restorations - Gabriela NISHIOKA; Catina PROCHNOW; Aline FIRMINO; Marina AMARAL; Marco Antonio BOTTINO; Luiz Felipe VALANDRO; MELO Renata Marques de (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract This in vitro study evaluated the fatigue strength of different ceramic materials indicated for monolithic restorations. Disc-shaped specimens were made according to ISO 6872 from five different ceramic materials: feldspathic ceramic (FC), polymer-infiltrated ceramic network (PIC), lithium disilicate glass-ceramic (LD), zirconia-reinforced lithium silicate glass-ceramic (ZLS), and high translucent tetragonal zirconia polycrystals doped by yttrium (YZ-HT). After obtaining the mean of each material (n = 5) from monotonic load-to-failure tests, specimens (n = 20) were subjected to fatigue tests (staircase method) using a biaxial flexural setup (piston-on-three-balls), to determine the fatigue strength. The parameters used for fatigue tests were: 100,000 cycles at 10 Hz, initial load of ~ 60% of mean load-to-failure, and step size of 5% of the initial load (specific for each ceramic material). Kruskal-Wallis and Bonferroni's test (α = 0.05) were used to analyze the fatigue strength data. Fatigue strength (MPa) of the materials was statistically different among each other as follows: YZ-HT (370.2 ± 38.7) > LD (175.2 ± 7.5) > ZLS (152.1 ± 7.5) > PIC (81.8 ± 3.9) > FC (50.8 ± 1.9). Thus, it can be concluded that, in terms of fatigue, high translucent polycrystalline zirconia is the best choice for monolithic restorations as it bears the highest load before cracking/fracturing.